SEMIOTICS ANALYSIS OF PUNJABI’S SIKH WEDDING CEREMONY AT GURGWARA SHREE GURU NANAK DEV JI MEDAN - Sheetal Sheetal; Muhammad Kiki Wardana (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2022)
Marriage is carried out through religious rules or customs. Almost similar to Indonesian culture which has several processions of a series of wedding ceremonies, Punjabi traditions consist of various cultural and religious customs. This research is focused on Indian wedding culture and this research was also conducted to find out what signs and symbols are found in Punjabi Sikh Wedding Ceremonies and how they are used. The theory used in this research is Pierce's Semiotics Theory. The location in this research will be conducted in Gurdwara Shree Guru Nanak Dev Ji Medan. This type of research is a qualitative research with descriptive method which aims to provide an objective description of a situation in the field with data collection techniques carried out by interviews, documentation, interviews and questionnaires.